A polyamide acid, a method for producing the same, a liquid crystal aligning agent, a liquid crystal aligning film, and a liquid crystal display element
Patent Information
- Application Number
- CN202610785560.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-06-02
AI Technical Summary
[0004]1.储存稳定性下降:游离酸酐活性高,可与体系中的微量水分反应生成游离酸,导致聚酰胺酸分子链降解,取向剂粘度下降,储存期缩短
[0042]本发明的聚酰胺酸制备方法,通过在反应全程保持二胺过量,可确保所有二酐单体均参与反应并被完全消耗,从根本上解决了因游离酸酐导致的取向剂储存稳定性差和液晶污染的问题。同时得到的液晶取向膜具有更高的电压保持率和更低的图像残留,特别适用于高分辨率、高刷新率液晶显示面板。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of LCD material display technology, specifically to a polyamic acid and its preparation method, a liquid crystal alignment agent, a liquid crystal alignment film, and a liquid crystal display element. Background Technology
[0002] Polyimide (PI) is the core material of the alignment layer in liquid crystal displays (LCDs), and its performance directly determines the quality of the display. Polyimide alignment agents are usually formed by the condensation polymerization of dianhydride monomers and diamine monomers in a solvent to produce polyamic acid (PAA), which is then coated and thermally imidized to form a PI film.
[0003] In traditional polyimide synthesis processes, equimolar amounts of dianhydride and diamine are typically used to ensure the completion of the polymerization reaction. However, in actual production, due to factors such as feeding errors, monomer purity fluctuations, or incomplete reactions, trace amounts of free anhydride monomer often remain in the system. These residual free anhydrides can cause a series of serious problems during orientation agent storage or subsequent film formation:
[0004] 1. Decreased storage stability: Free anhydrides are highly reactive and can react with trace amounts of moisture in the system to generate free acids, leading to the degradation of polyamic acid molecular chains, a decrease in the viscosity of the orientation agent, and a shortened shelf life.
[0005] 2. Liquid crystal contamination: Residual acid anhydrides or their hydrolysis products may volatilize or migrate to the surface of the film during high-temperature curing, contaminating the liquid crystal material and causing a decrease in voltage retention rate (VHR) and a deterioration in image retention (ACIS).
[0006] 3. Thin film defects: Free anhydride may form micro-aggregates in the thin film, causing film inhomogeneity or crystal points, affecting orientation quality and display effect.
[0007] To address the issue of residual free anhydride, existing technologies often employ strict control of the feed ratio or add post-treatment purification steps. However, these methods increase process complexity and cost, and are difficult to completely eliminate the residue.
[0008] Furthermore, existing technologies lack systematic research on the influence of the ratio between diamine monomers, the selection of anhydride monomers, and their ratio on the final polyimide molecular chain sequence structure, resulting in an unclear structure-property relationship between polymer structure and properties, making it difficult to achieve precise control of performance. Summary of the Invention
[0009] To address the aforementioned technical problems, this invention provides a polyamic acid and its preparation method, a liquid crystal alignment agent, a liquid crystal alignment film, and a liquid crystal display element, which avoids the residue of free anhydride and achieves precise control over the functional group sequence and distribution in the final polymer chain.
[0010] The present invention adopts the following technical solution:
[0011] In a first aspect, the present invention provides a method for preparing polyamic acid, comprising the following steps:
[0012] Under nitrogen protection, diamine monomers A and B are dissolved in an organic solvent, dianhydride monomer G1 is added and stirred continuously. After the dianhydride monomer G1 is completely consumed by the reaction, dianhydride monomer G2 is added and stirred to obtain the product.
[0013] Wherein, the ratio of the total molar amount of the diamine monomer A and the diamine monomer B to the total molar amount of the dianhydride monomer G1 and the dianhydride monomer G2 is greater than 1;
[0014] The reactivity of the dianhydride monomer G1 is less than that of the dianhydride monomer G2, and the reactivity is the relative reaction rate of the ring-opening nucleophilic addition reaction between the anhydride group and the amino group.
[0015] With the relative reaction rate of pyromellitic dianhydride as 1, the relative reaction rate of dianhydride monomer G1 is <0.3, and the relative reaction rate of dianhydride monomer G2 is ≥0.6.
[0016] Furthermore, the ratio R1 of the total molar amount of the diamine monomer A and the diamine monomer B to the molar amount of the dianhydride monomer G1 satisfies 1.1≤R1≤2.0.
[0017] Furthermore, the molar ratio γ of the dianhydride monomer G2 and the dianhydride monomer G1 satisfies 0.2≤γ≤2.0.
[0018] Furthermore, the ratio δ of the total molar amount of the diamine monomer A and the diamine monomer B to the total molar amount of the dianhydride monomer G1 and the dianhydride monomer G2 satisfies 1.00 < δ ≤ 1.50.
[0019] Furthermore, the diamine monomer A is a diamine monomer without functional groups, and the diamine monomer B is a diamine monomer containing functional groups.
[0020] Furthermore, the molar ratio α of the diamine monomer A and the diamine monomer B satisfies 0 < α ≤ 1.0.
[0021] Secondly, the present invention also provides a polyamic acid prepared by the above preparation method, comprising the following structure:
[0022]
[0023] Polymer PAA-AA
[0024]
[0025] Polymer PAA-AB
[0026]
[0027] Polymer PAA-BB
[0028]
[0029] Polymer (PAA-AA)-G2-(PAA-AA)
[0030]
[0031] Polymer (PAA-AA)-G2-(PAA-AB)
[0032]
[0033] Polymer (PAA-AA)-G2-(PAA-BB)
[0034]
[0035] Polymer (PAA-BB)-G2-(PAA-BB)
[0036]
[0037] Polymer (PAA-BB)-G2-(PAA-AB)
[0038] Wherein, G1 and G2 are tetravalent organic groups, A and B are divalent organic groups, and n1, n2, and n3 represent the number of polymerization units, ranging from 50 to 1000.
[0039] Thirdly, the present invention also provides a liquid crystal alignment agent, comprising polyamic acid and / or polyimide obtained by imidizing the polyamic acid, wherein the polyamic acid is the above-mentioned polyamic acid or polyamic acid prepared by the above-mentioned preparation method.
[0040] Fourthly, the present invention also provides a liquid crystal alignment film, which is obtained by coating and baking the above-mentioned liquid crystal alignment agent.
[0041] Fifthly, the present invention also provides a liquid crystal display element comprising the above-described liquid crystal alignment film.
[0042] The polyamic acid preparation method of this invention ensures that all dianhydride monomers participate in the reaction and are completely consumed by maintaining an excess of diamine throughout the reaction, fundamentally solving the problems of poor storage stability of alignment agents and liquid crystal contamination caused by free anhydrides. Simultaneously, the resulting liquid crystal alignment film exhibits higher voltage retention and lower image retention, making it particularly suitable for high-resolution, high-refresh-rate liquid crystal display panels.
[0043] The preparation method of this invention uses a dianhydride with low reactivity to react with a diamine first. The low reactivity of the dianhydride monomer G1 ensures that the reaction is controllable and imparts moderate flexibility to the prepolymer. Then, a dianhydride monomer with high reactivity G2 is added. Its high reactivity allows for rapid chain growth and precise embedding of high-rigidity segments into the molecular chain. This achieves independent design of the "mechanical property module" and the "interface functional module", enabling precise control of the polymer chain structure. Detailed Implementation
[0044] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.
[0045] This invention provides a method for preparing polyamic acid, comprising the following steps:
[0046] Under nitrogen protection, diamine monomers A and B are dissolved in an organic solvent, dianhydride monomer G1 is added and stirred continuously. After the dianhydride monomer G1 is completely consumed by the reaction, dianhydride monomer G2 is added and stirred to obtain the product.
[0047] Wherein, the ratio of the total molar amount of the diamine monomer A and the diamine monomer B to the total molar amount of the dianhydride monomer G1 and the dianhydride monomer G2 is greater than 1;
[0048] The reactivity of the dianhydride monomer G1 is less than that of the dianhydride monomer G2. The reactivity is the relative reaction rate of the ring-opening nucleophilic addition reaction between the anhydride group (-CO-O-CO-) in the dianhydride monomer and the amino group (-NH2) in the diamine monomer.
[0049] With the relative reaction rate of pyromellitic dianhydride as 1, the relative reaction rate of dianhydride monomer A is <0.3, and the relative reaction rate of dianhydride monomer B is ≥0.6.
[0050] The polyamic acid preparation method of this invention ensures that all dianhydride monomers participate in the reaction and are completely consumed by maintaining an excess of diamine throughout the reaction, fundamentally solving the problems of poor storage stability of alignment agents and liquid crystal contamination caused by free anhydrides. The amino-terminated polyamic acid solution is less prone to degradation during storage, exhibits stable viscosity, and has a significantly extended shelf life. Alignment films formed with alignment agents free of residual anhydrides have higher voltage retention and lower image retention, making them particularly suitable for high-resolution, high-refresh-rate liquid crystal display panels.
[0051] Simultaneously, a low-reactivity dianhydride is first reacted with a diamine. The low reactivity of the dianhydride monomer G1 ensures the controllability of the reaction and imparts moderate flexibility to the prepolymer, constructing flexible / medium-rigid chain segments. Then, a highly reactive dianhydride monomer G2 is added, utilizing its high reactivity to rapidly complete chain growth and precisely embed the high-rigidity chain segments into the molecular chain. This achieves independent design of the "mechanical property module" and the "interface functional module," enabling precise control of the polymer chain structure.
[0052] Specifically, in some embodiments of the present invention, the reactivity of dianhydride monomers is influenced by both electronic and steric effects of their molecular structure. The high reactivity of acid anhydrides stems from their unique electronic structure: the oxygen atom in an anhydride is sandwiched between two carbonyl groups, forcing its lone pair electrons to delocalize simultaneously to both carbonyl groups (cross-conjugation effect). This reduces the degree of electron stabilization for each carbonyl carbon, thus making the carbonyl carbon exhibit stronger electrophilicity and more susceptible to nucleophilic attack from amino groups.
[0053] The differences in activity among similar acid anhydrides mainly depend on the following structural factors:
[0054] (1) Aromatic anhydrides > Alicyclic anhydrides: Aromatic anhydrides (such as pyromellitic dianhydride PMDA and 3,3',4,4'-biphenyltetracarboxylic dianhydride BPDA) have anhydride groups directly attached to the aromatic ring. The conjugation effect of the aromatic ring enhances the electrophilicity of the carbonyl carbon. At the same time, the rigid structure of the aromatic ring reduces steric hindrance, so the reactivity is high. Alicyclic anhydrides (such as 1,2,3,4-cyclobutanetetracarboxylic dianhydride CBDA and 1,2,4,5-cyclohexanetetracarboxylic dianhydride HPMDA) have anhydride groups attached to the saturated cycloalkane structure. There is no conjugation effect, and the electrophilicity of the carbonyl carbon is weak. At the same time, the steric hindrance of the alicyclic structure is large, which is not conducive to the approach of the amino group, so the reactivity is low.
[0055] (2) Cyclic anhydrides (such as CBDA and phthalic anhydride) > acyclic anhydrides: This is because atoms in a cyclic structure are forced into a non-natural geometric arrangement, generating ring strain. When a nucleophile attacks a cyclic anhydride, the ring-opening reaction releases the stored ring strain, lowers the activation energy of the reaction, and makes the reaction easier to proceed. Five-membered cyclic anhydrides have greater ring strain and higher reactivity than six-membered cyclic anhydrides.
[0056] (3) Electronic effects of substituents: Electron-withdrawing substituents (such as -F, -Cl, -CF3, -NO2) further enhance the electrophilicity of carbonyl carbon through inductive effect and improve the reactivity of acid anhydrides; electron-donating substituents (such as -CH3, -OCH3) reduce the electrophilicity of carbonyl carbon and reduce reactivity.
[0057] Based on the above principles, dianhydride monomer G1 is a low-reactivity acid anhydride, and dianhydride monomer G2 is a high-reactivity acid anhydride. Reactivity is determined by the relative reaction rate; specifically, the experimental determination method is as follows:
[0058] Under standard reaction conditions (solvent: N-methylpyrrolidone (NMP), temperature: 25±1°C, acid anhydride reacting with p-phenylenediamine (PDA) in equimolar amounts, with an initial concentration of 0.05 mol / L), the relative reaction rate constant was calculated by monitoring the decay rate of the characteristic infrared absorption peaks (1780 cm⁻¹ and 1850 cm⁻¹) of the acid anhydride in the reaction system.
[0059] Using pyromellitic dianhydride (PMDA) as a reference, and setting its relative reaction rate to 1.00, the relative reaction rate of the anhydride to be tested was calculated using the following formula:
[0060] Relative reaction rate = K 酸酐 / K PMDA ;
[0061] Grading threshold:
[0062] Second dianhydride monomer (G2 type): relative reaction rate ≥ 0.60;
[0063] First dianhydride monomer (G1 type): relative reaction rate < 0.30.
[0064] In the preparation method of this invention, the dianhydride monomer G1 with low reactivity is first reacted with an excess of mixed diamines. The dianhydride monomer G1 is completely consumed, generating a prepolymer with amino-terminated ends. After the dianhydride monomer G1 is completely consumed, the highly reactive dianhydride monomer G2 is added. The dianhydride monomer G2 reacts with the excess diamine in the system (including the unreacted free diamine from the first step and the amino-terminated ends of the prepolymer) to further increase the polymer chain. Through the above stepwise feeding process, a polyamic acid with amino-terminated ends and no free anhydride is finally obtained. Its chain segment sequence is composed of the backbone constructed in the first step (mainly containing G1 units) and the chain segments formed by the highly reactive anhydride G2 introduced in the second step.
[0065] Specifically, in some embodiments of the present invention, the method for determining whether the dianhydride monomer G1 has been completely consumed in the reaction is as follows: a small amount of the reaction solution is taken for infrared spectroscopy detection to confirm that the reaction time is 1730 cm⁻¹. -1 The complete disappearance of the characteristic absorption peak of the acid anhydride at the location proves that there is no free acid anhydride residue.
[0066] Specifically, in some embodiments of the present invention, the dianhydride monomer G1 includes any one of the following compounds:
[0067]
[0068] The dianhydride monomer G2 includes any one of the following compounds:
[0069]
[0070] The low-reactivity dianhydride monomer G1 reacts slowly and controllably with the diamine in the first step under excess diamine conditions, ensuring uniform reaction and avoiding localized overheating or explosive polymerization. Its alicyclic structure imparts a certain degree of flexibility to the molecular chain, balancing the brittleness caused by the high-rigidity framework, allowing the film to maintain high modulus while possessing sufficient toughness to withstand processing stress. The highly reactive dianhydride monomer G2 reacts rapidly with the excess diamine in the system upon its addition in the second step, completing molecular chain growth and segmental connection. Its aromatic rigid structure imparts high segmental rigidity to the molecular chain, which is the key source of the film's high modulus and high thermal stability. By introducing it in the second step, it can be precisely positioned at specific locations (connection points) in the molecular chain, avoiding interference with the framework structure constructed in the first step.
[0071] Specifically, in some embodiments of the present invention, the ratio of the total molar amount of diamine monomer A and diamine monomer B to the molar amount of dianhydride monomer G1 is R1 = [n(A) + n(B)] / n(G1). By adjusting R1, the chain length and terminal amino density of the prepolymer after the first step reaction are controlled. When R1 is close to 1.0, the prepolymer chain length is relatively long and the terminal amino density is low, and the second step reaction tends to connect the prepolymer to form a long chain. When R1 is relatively large, the prepolymer chain length is relatively short and the terminal amino density is high, and the second step reaction easily forms a branched structure or a product with a wide molecular weight distribution. Preferably, the ratio of the total molar amount of the diamine monomer A and the diamine monomer B to the molar amount of the dianhydride monomer G1 satisfies 1.1 ≤ R1 ≤ 2.0; more specifically, R1 is a range of 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any combination thereof; more preferably, 1.2 ≤ R1 ≤ 1.8, to obtain a suitable prepolymer chain length and good reaction controllability.
[0072] Specifically, in some embodiments of the present invention, the molar ratio γ = n(G2) / n(G1) of the dianhydride monomer G2 and the dianhydride monomer G1 satisfies 0.2 ≤ γ ≤ 2.0. By controlling the length ratio of G1 and G2 segments through γ, the rigidity, thermal properties, and charge transport characteristics of the polymer are directly affected. When γ is small (low G2 ratio), the polymer is dominated by flexible or medium-rigid segments formed by G1, resulting in good film flexibility and moderate modulus. When γ is large (increased G2 ratio), the proportion of high-rigidity segments formed by G2 increases, significantly improving the elastic modulus of the film, making it suitable for applications requiring high hardness. More specifically, the molar ratio γ of the dianhydride monomer G2 and the dianhydride monomer G1 is a range of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any combination thereof; preferably, 0.3 ≤ γ ≤ 1.5, within which synergistic optimization of modulus and toughness can be achieved.
[0073] Specifically, in some embodiments of the present invention, the ratio of the total molar amount of the diamine monomer A and the diamine monomer B to the total molar amount of the dianhydride monomer G1 and the dianhydride monomer G2, δ = [n(A) + n(B)] / [n(G1) + n(G2)], satisfies 1.00 < δ ≤ 1.50. To satisfy the diamine excess, ensuring that the system has no acid anhydride residue and that the chain ends are amino, δ > 1; when δ approaches 1, a perfectly amino-terminated linear polymer is obtained; when δ > 1, a polymer with amino excess is obtained, which can provide additional reaction sites for post-modification or enhanced adhesion. Since the presence of excess free diamine in the system will reduce the storage stability of the polymer, δ is controlled at 1.00 < δ ≤ 1.50, that is, diamine excess but not exceeding 50%, to obtain a polymer system with amino end-capping and excellent performance. More specifically, the ratio δ of the total molar amount of the diamine monomer A and the diamine monomer B to the total molar amount of the dianhydride monomer G1 and the dianhydride monomer G2 is 1.01, 1.05, 1.08, 1.1, 1.12, 1.15, 1.19, 1.2, 1.23, 1.25, 1.27, 1.3, 1.32, 1.35, 1.38, 1.4, 1.42, 1.45, 1.48, 1.5, or any intermediate value of both. Preferably, 1.00 < δ < 1.20.
[0074] Specifically, in some embodiments of the present invention, the diamine monomer A is a diamine monomer without functional groups, and the diamine monomer B is a diamine monomer containing functional groups.
[0075] In this invention, a functional group refers to a functional group in the molecular structure that has specific chemical properties and plays a specific role in the reaction; the diamine monomer A refers to a diamine molecule that does not contain any active functional groups other than amino groups that can interact with liquid crystal molecules or significantly affect the surface chemical properties of the film. The diamine monomer B refers to a diamine molecule that contains functional functional groups other than amino groups, and these functional groups can regulate the interfacial properties of the polyimide film.
[0076] Specifically, diamine monomer A has a rigid backbone structure, containing no or only substituents that do not affect the rigidity of the main chain, and has low rotational freedom of the molecular chain segments. The functional groups in diamine monomer B include any one or more of hydroxyl, carboxyl, amino, C1-C6 alkoxy, cyano, vinyl, epoxy, mercapto, amide, ester, and fluorine-containing groups. It can be further classified into: polar group type (-OH, -COOH, -NH2, -CN), providing charge trapping ability and enhancing adhesion; crosslinking reaction type (vinyl), providing thermal or photocrosslinking reaction sites; and surface energy modulating type (-CF3, long-chain alkoxy), regulating the surface energy of the film.
[0077] Diamine monomer A is mainly used to regulate the mechanical properties of the molecular chain, and is responsible for the bulk properties of polyimide films such as elastic modulus, tensile strength, dimensional stability, and thermomechanical properties. The rigid skeleton structure gives the molecular chain a high degree of segment rigidity, forming a dense molecular stack after film formation, providing high modulus support to resist frictional orientation shear forces, ensuring that the film does not generate debris or scratches during the friction process, while ensuring dimensional stability under high-temperature processes.
[0078] Diamine monomer B primarily regulates the interfacial properties of the molecular chain, responsible for the surface tension, liquid crystal alignment capability, charge trapping and image retention suppression, compatibility with liquid crystals, and adhesion of polyimide films. Specifically, image retention suppression: polar groups (such as -OH, -COOH) can trap and fix mobile ionic impurities in the liquid crystal, blocking charge migration paths, thereby significantly reducing AC image retention (ACIS); surface tension regulation: functional groups with different surface energies (such as hydrophilic -OH or hydrophobic -CF3) accumulate on the surface during film formation, directly changing the surface chemical composition of the film and achieving precise control of the pretilt angle and liquid crystal alignment; enhanced adhesion: active groups (such as epoxy groups, -COOH) can form chemical bonds with hydroxyl groups on the substrate surface, improving the adhesion between the film and the glass substrate.
[0079] Specifically, in some embodiments of the present invention, the diamine monomer A includes any one of p-phenylenediamine, benzidine, 4,4'-diaminodiphenylmethane, 9-methyl-9H-fluorene-2,7-diamine, and 2,2'-dimethylbiphenyl.
[0080] Specifically, in some embodiments of the present invention, the diamine monomer B comprises any one of the following compounds:
[0081]
[0082]
[0083] .
[0084] Specifically, in some embodiments of the present invention, the molar ratio α of the first diamine monomer A and the second diamine monomer B, α = n(A) / n(B), satisfies 0 < α ≤ 1.0; α determines the relative proportion of the two diamines in the first step reaction, directly affecting the distribution density of A and B structural units in the prepolymer. When α is small, A units dominate in the prepolymer, and B units are distributed as sparse "functional points" in the chain, suitable for scenarios requiring stable main body performance; when α is large, the proportion of B units in the prepolymer increases, and B units may form continuous functional segments, increasing the surface functional group density, which can significantly regulate the interfacial properties of the film (such as surface tension and compatibility with liquid crystals). Preferably, the molar ratio α of the first diamine monomer A and the second diamine monomer B satisfies 0.1 ≤ α ≤ 0.5, within which functional groups can be effectively introduced while ensuring the performance of the main body framework.
[0085] The polyamic acid preparation method of this invention employs a "diamine excess-step anhydride addition" polymerization process, and controls the type and order of addition of dianhydride monomers. This ensures that all anhydrides are completely consumed during the reaction, resulting in a final system free of free anhydrides and molecular chains terminated with amino groups. Simultaneously, it achieves precise design of the molecular chain sequence structure. Specifically:
[0086] Diamine monomer A (rigid) and dianhydride monomer G2 (highly reactive aromatic) can form highly rigid segments responsible for the mechanical framework of the film; diamine monomer B (functional group) and dianhydride monomer G1 (lowly reactive alicyclic) can form functional segments responsible for the interfacial properties of the film.
[0087] In the preparation process, dianhydride monomer G1 is first reacted with mixed diamines. The low reactivity of dianhydride monomer G1 ensures that the reaction is controllable, while the alicyclic structure of dianhydride monomer G1 endows the prepolymer with moderate flexibility. Then, dianhydride monomer G2 is added to rapidly complete chain growth by utilizing its high reactivity, and the high-rigidity chain segment is precisely embedded into the molecular chain. Through the above classification design, this invention realizes the independent design of the "mechanical property module" and the "interface function module", which fundamentally solves the technical bottleneck of mutual restriction between the two properties in the traditional random copolymerization method.
[0088] Specifically, in some embodiments of the present invention, the stirring time after adding dianhydride monomer G1 or dianhydride monomer G2 is 3 to 12 hours.
[0089] Specifically, in some embodiments of the present invention, the organic solvents mentioned above are not specifically limited to any solvent that can dissolve the generated polyamic acid. Examples include: N,N-dimethylformamide, N-methyl-2-pyrrolidone, N-methylcaprolactam, dimethyl sulfone, pyridine, isopropanol, diethylene glycol dimethyl ether, ethylene glycol butyl ether, n-hexane, methyl acetate, etc. These organic solvents can be used alone or in combination.
[0090] Secondly, the present invention also provides a polyamic acid, prepared by the above-described preparation method, comprising the following structure:
[0091]
[0092] Polymer PAA-AA
[0093]
[0094] Polymer PAA-AB
[0095]
[0096] Polymer PAA-BB
[0097]
[0098] Polymer (PAA-AA)-G2-(PAA-AA)
[0099]
[0100] Polymer (PAA-AA)-G2-(PAA-AB)
[0101]
[0102] Polymer (PAA-AA)-G2-(PAA-BB)
[0103]
[0104] Polymer (PAA-BB)-G2-(PAA-BB)
[0105]
[0106] Polymer (PAA-BB)-G2-(PAA-AB)
[0107] Wherein, G1 and G2 are tetravalent organic groups, A and B are divalent organic groups, and n1, n2, and n3 represent the number of polymerization units, ranging from 50 to 1000.
[0108] In each polymer, A corresponds to the group in diamine monomer A after removing the amino groups at both ends, B corresponds to the group in diamine monomer B after removing the amino groups at both ends; G1 corresponds to the group in dianhydride monomer G1 after removing the anhydride, and G2 corresponds to the group in dianhydride monomer G2 after removing the anhydride.
[0109] The present invention also provides a liquid crystal alignment film, which is obtained by coating and baking the above-mentioned liquid crystal alignment agent.
[0110] The present invention also provides a liquid crystal display element, including the above-described liquid crystal alignment film.
[0111] The liquid crystal alignment agent of the present invention will be further described below with reference to specific embodiments.
[0112] Example 1
[0113] raw material:
[0114] Diamine monomer A: p-phenylenediamine (PDA) ;
[0115] Diamine monomer B: Diaminodiphenylamine (NDA) (Compound B-17);
[0116] Dianhydride monomer G1 (low reactivity): 1,2,3,4-cyclobutanediol dianhydride (CBDA) (Compound G1-1);
[0117] Dianhydride monomer G2 (highly reactive): Pyromellitic dianhydride (PMDA) (Compound G2-1).
[0118] The preparation method of polyamic acid in this embodiment is as follows:
[0119] Under nitrogen protection, 0.2 mol of p-phenylenediamine (PDA) and 0.6 mol of diaminodiphenylamine (NDA) were dissolved in NMP (N-methyl-2-pyrrolidone), stirred until the solid was completely dissolved, and then cooled to 15°C.
[0120] 0.5 mol of 1,2,3,4-cyclobutanediol dianhydride (CBDA) was added, and the reaction was carried out for 4 hours. A small amount of the reaction solution was taken for infrared spectroscopy detection, which confirmed that the characteristic absorption peak of the anhydride at 1730 cm⁻¹ had completely disappeared, indicating that CBDA had been completely consumed and a prepolymer with amino groups at the end was generated.
[0121] Add 0.28 mol of pyromellitic dianhydride (PMDA) and continue the reaction for 12 h to obtain a polyamic acid solution with amino groups at both ends and a viscosity of approximately 1200 cp.
[0122] The reaction process is as follows:
[0123]
[0124] Examples 2-38 and Comparative Examples 1-7
[0125] Examples 2-38 and Comparative Examples 1-7 are basically the same as Example 1, except that the content and category of each component are different in Tables 1-5.
[0126] Comparative Example 8
[0127] The difference between this comparative example and Example 1 is that the preparation order is changed to first adding dianhydride monomer G2, and then adding dianhydride monomer G1. Specifically:
[0128] The preparation method of polyamic acid in this comparative example is as follows:
[0129] Under nitrogen protection, 0.2 mol of p-phenylenediamine (PDA) and 0.6 mol of diaminodiphenylamine (NDA) were dissolved in NMP (N-methyl-2-pyrrolidone), stirred until the solid was completely dissolved, and then cooled to 15°C.
[0130] 0.28 mol of pyromellitic dianhydride (PMDA) was added, and the reaction was carried out for 12 h. A small amount of the reaction solution was taken for infrared spectroscopy detection, which confirmed that the characteristic absorption peak of the anhydride at 1730 cm⁻¹ had completely disappeared, and PMDA had been completely consumed, generating a prepolymer with amino groups at the end.
[0131] Add 0.5 mol of 1,2,3,4-cyclobutanediol dianhydride (CBDA) and react for 4 hours to obtain a polyamic acid solution with amino groups at both ends.
[0132] Comparative Example 9
[0133] The difference between this comparative example and Example 1 is that the preparation order is changed to the simultaneous addition of dianhydride monomer G2 and dianhydride monomer G1. Specifically:
[0134] The preparation method of polyamic acid in this comparative example is as follows:
[0135] Under nitrogen protection, 0.2 mol of p-phenylenediamine (PDA) and 0.6 mol of diaminodiphenylamine (NDA) were dissolved in NMP (N-methyl-2-pyrrolidone), stirred until the solid was completely dissolved, and then cooled to 15°C.
[0136] 0.28 mol of pyromellitic dianhydride (PMDA) and 0.5 mol of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) were added, and the reaction was carried out for 12 h to obtain a polyamic acid solution with amino groups at both ends.
[0137] The polyamic acid prepared in each embodiment and comparative example was used to prepare liquid crystal alignment films, and its performance was tested.
[0138] Test method:
[0139] 1. Image retention performance test
[0140] 1.1 Test Principle
[0141] Image retention refers to the phenomenon where a liquid crystal display module retains traces of the previous image after displaying the same static image for an extended period and then switching to another image. The mechanism is as follows: ionic impurities within the liquid crystal cell migrate and remain on the alignment film surface under the influence of an electric field, creating a DC bias voltage that causes abnormal rotation angles of the liquid crystal molecules.
[0142] 1.2 Sample Preparation
[0143] 1.2.1 Preparation of liquid crystal alignment film
[0144] After filtering the polyimide alignment agent through a 1.0 μm pore size filter, it was spin-coated onto a prepared electrode substrate and a glass substrate with an ITO film on the back and columnar spacers with a height of 4 μm. The coated surface was dried on a hot plate at 80°C for 5 minutes, then irradiated with linearly polarized ultraviolet light of 254 nm wavelength with an extinction ratio of 26:1 through a polarizer. Finally, it was fired in a hot air circulating oven at 230°C for 30 minutes to obtain a substrate with a liquid crystal alignment film.
[0145] The two substrates obtained above are grouped together, and a sealant is printed on the substrates. Another substrate is then bonded together with its liquid crystal alignment film facing each other at 0°. The sealant is then cured to create a blank cell. Liquid crystal is injected into the blank cell using a reduced-pressure injection method, and the injection port is sealed to obtain a liquid crystal cell. The resulting liquid crystal cell is then heated at 120°C for 1 hour and left to stand overnight to evaluate the image retention caused by long-term AC driving.
[0146] 1.3 Test Conditions
[0147] The liquid crystal cell fabricated above was subjected to an AC voltage of 60Hz ±5V for 120 hours at a constant temperature of 60℃. Then, the pixel electrode and the counter electrode of the liquid crystal cell were short-circuited, and this state was maintained at room temperature for one day.
[0148] Regarding the liquid crystal cell that has undergone the above processing, the offset between the orientation direction of the liquid crystal in the first region and the orientation direction of the liquid crystal in the second region of the pixel when no voltage is applied is calculated in terms of angle. Specifically, the liquid crystal cell is placed between two polarizing plates arranged orthogonally to each other on their polarization axes, and then the liquid crystal cell is lit.
[0149] The backlight is adjusted so that the transmitted light intensity of the first region of the pixel is minimized. Then, the rotation angle required to rotate the liquid crystal cell is determined so that the transmitted light intensity of the second region of the pixel is minimized.
[0150] 1.4 Evaluation of Afterimage Level
[0151] The smaller the value of this rotation angle, the better the afterimage characteristics based on long-term AC drive. Specifically, a rotation angle ≤ 0.5° is rated as "excellent", 0.5° < rotation angle ≤ 1.0° is rated as "average", and rotation angle > 1.0° is rated as "unacceptable".
[0152] 2. Voltage Holding Rate Test Method
[0153] 2.1 Test equipment: VHR test system (TOYO Model 6254).
[0154] 2.2 The preparation of the test cell is consistent with that of the afterimage test in 1.2.1.
[0155] 2.3 Test conditions:
[0156] Temperature: 85℃ (High-temperature testing is more stringent and can better distinguish between good and bad performance).
[0157] Applied voltage: 5 V (simulating actual driving voltage).
[0158] Voltage application time (t1): 60 ms.
[0159] Hold time (t2): 500 ms.
[0160] Test waveform: square wave.
[0161] 2.4 Operating Steps:
[0162] Place the test box on a temperature-controlled platform, heat it to the set temperature (85℃), and stabilize it for 30 minutes. Apply a 5V, 60ms square wave voltage to the test box. After removing the voltage, delay for a very short time (1ms) and begin measuring the remaining voltage decay curve.
[0163] Calculation formula:
[0164] Among them, V applied It is the applied voltage (5V), V after It is the remaining voltage after the holding time (500ms).
[0165] 2.5 Voltage Holding Rate Rating Evaluation
[0166] The higher the VHR value, the better the voltage holding rate. Specifically, VHR (85°C, 5V, 500ms) ≥ 95% is rated as "excellent", 90% ≤ VHR (85°C, 5V, 500ms) < 95% is rated as "average", and VHR (85°C, 5V, 500ms) < 90% is rated as "unacceptable".
[0167] 3. Thin film defect assessment
[0168] 3.1 Test method: Surface roughness method
[0169] 3.2 Sample preparation: The liquid crystal alignment agent was coated onto a clean substrate according to the standard process, and a polyimide film with a thickness of 80-120 nm was prepared by pre-baking (80℃ / 5min) and curing baking (180-230℃ / 30-60min, N2 atmosphere).
[0170] 3.3 Test Methods
[0171] The surface morphology of the polyimide film was scanned using atomic force microscopy (AFM), and the surface roughness (Ra) was measured. The test conditions were as follows:
[0172] Scanning Mode: Tapping Mode
[0173] Scan range: 5μm × 5μm or 10μm × 10μm
[0174] Scan frequency: 0.5-1.0 Hz
[0175] Number of test points: ≥5 different regions per sample
[0176] Environmental conditions: 23±2℃, 45±5% RH
[0177] 3.4 Evaluation of Thin Film Defect Levels
[0178] The smaller the surface roughness (Ra) value, the higher the defect level of the thin film. Specifically, Ra ≤ 0.5 nm is rated as "excellent", 0.5 nm < Ra ≤ 1.0 nm is rated as "average", and Ra > 1.0 nm is rated as "unacceptable".
[0179] 4. Storage stability evaluation
[0180] 4.1 Sample preparation: The polyamic acid solution was dispensed into sealed PFA plastic bottles and stored under the following conditions: refrigerated storage: -18±2℃;
[0181] Test environment requirements: relative humidity ≤50%, temperature 23±2℃.
[0182] 4.2 Test Methods
[0183] The viscosity of the polyamic acid solution was determined using a cone-plate viscometer. The test conditions were as follows:
[0184] Measurement range: 3-6000 cP
[0185] Temperature holding time: 5 min
[0186] Test temperature: 25±0.1℃ (constant temperature water bath)
[0187] Rotation speed: Select according to viscosity range
[0188] 4.3 Storage stability level evaluation
[0189] When stored at -18±2℃ for 120 days, a viscosity change rate ≤10% is rated as "Excellent"; 10% < viscosity change rate ≤20% is rated as "Pass"; and 20% < viscosity change rate is rated as "Fail".
[0190] Tables 1-6 show the relevant parameters and test results for each embodiment and comparative example.
[0191] Table 1 shows the test results of Examples 1-17 and Comparative Examples 1-5. The difference between Examples 2-17, Comparative Examples 1-5 and Example 1 lies only in the relevant parameters in Table 1, mainly the contents of diamine monomer A, diamine monomer B, dianhydride monomer G1, and dianhydride monomer G2.
[0192] Table 1
[0193]
[0194]
[0195] Note: " / " indicates that the item is not included.
[0196] As can be seen from the test results in Table 1, by using the preparation method of the present invention, maintaining an excess of diamine throughout the reaction process ensures that all dianhydride monomers participate in the reaction and are completely consumed. Simultaneously, the low-reactivity dianhydride reacts with the diamine first, utilizing the low reactivity of dianhydride monomer G1 to ensure controllable reaction and impart moderate flexibility to the prepolymer, constructing flexible / medium-rigid segments. Then, the highly reactive dianhydride monomer G2 is added, utilizing its high reactivity to rapidly complete chain growth and precisely embed the high-rigidity segments into the molecular chain. This achieves independent design of the "mechanical property module" and the "interface functional module," enabling precise control of the polymer chain structure. The resulting liquid crystal alignment film exhibits higher voltage retention and lower image residue, fundamentally solving the problems of poor storage stability of the alignment agent and liquid crystal contamination caused by free anhydrides.
[0197] As can be seen from the test results of Examples 1-17 and Comparative Examples 1-4, using only the low-activity dianhydride monomer G1, or only the high-activity dianhydride monomer G2, or only the diamine monomer A or diamine monomer B, is not conducive to the control of the reaction process, chain length, chain segment rigidity, etc., thus affecting the performance of the orientation agent and the orientation film. As can be seen from the test results of Examples 1-17 and Comparative Example 5, if the acid anhydride is in excess, the polyamic acid is capped with acid anhydride, and free acid anhydride exists, which seriously affects the storage stability of the polymer and causes film defects.
[0198] As can be seen from the test results of Examples 1-8 and Examples 9-17, when the ratio of the total molar amount of diamine monomer A and diamine monomer B to the molar amount of dianhydride monomer G1, R1=[n(A)+n(B)] / n(G1), satisfies 1.1≤R1≤2.0, the molar ratio of dianhydride monomer G2 and dianhydride monomer G1, γ=n(G2) / n(G1), satisfies 0.2≤γ≤2.0, the ratio of the total molar amount of diamine monomer A and diamine monomer B to the total molar amount of dianhydride monomer G1 and dianhydride monomer G2, δ, satisfies 1.00<δ≤1.50, or the molar ratio of the first diamine monomer A and the second diamine monomer B, α, satisfies 0<α≤1.0, a liquid crystal alignment agent with better storage stability can be obtained, and the voltage retention rate, image residue, and surface roughness of the prepared alignment film are further optimized. This is primarily because adjusting R1 allows control over the chain length and terminal amino group density of the prepolymer after the first reaction, contributing to a suitable prepolymer chain length and good reaction controllability. γ controls the length ratio of G1 and G2 segments, resulting in a polymer with appropriate rigidity. δ controls the degree of amino group excess, ensuring an amino-terminated polymer without affecting storage stability due to diamine excess. Controlling the magnitude of α ensures the performance of the main backbone while effectively introducing functional groups.
[0199] Table 2 shows the test results of Examples 1 and 18-21. The difference between Examples 18-21 and Example 1 lies only in the relevant parameters in Table 2, mainly the type of diamine monomer A.
[0200] Table 2
[0201]
[0202] As can be seen from the test results in Table 2, when the preparation method of the present invention is used, and the diamine is kept in excess throughout the reaction process, and a low-reactivity dianhydride is used to react with the diamine first, followed by the addition of a high-reactivity dianhydride monomer G2, an alignment agent with good storage stability can be obtained for different diamine monomers A. Moreover, the liquid crystal alignment film has a higher voltage retention rate, lower image residue, and lower surface roughness, indicating that the present invention has universality for different diamine monomers A.
[0203] Table 3 shows the test results of Examples 1 and Examples 22-28. The difference between Examples 22-28 and Example 1 lies only in the relevant parameters in Table 3, mainly the type of diamine monomer B.
[0204] Table 3
[0205]
[0206] As can be seen from the test results in Table 3, when the preparation method of the present invention is used, and the diamine is kept in excess throughout the reaction process, and a low-reactivity dianhydride is used to react with the diamine first, followed by the addition of a high-reactivity dianhydride monomer G2, an alignment agent with good storage stability can be obtained for different diamine monomers B. Moreover, the liquid crystal alignment film has a higher voltage retention rate, lower image residue, and lower surface roughness, indicating that the present invention has universality for different diamine monomers B.
[0207] Table 4 shows the test results of Examples 1, Examples 29-33, and Comparative Examples 6-7. The difference between Examples 29-33, Comparative Examples 6-7 and Example 1 lies only in the relevant parameters in Table 4, mainly the type of dianhydride monomer G1.
[0208] Table 4
[0209]
[0210] As can be seen from the test results in Table 4, when the preparation method of the present invention is used, and the diamine is kept in excess throughout the reaction process, and a low-reactivity dianhydride is used to react with the diamine first, followed by the addition of a high-reactivity dianhydride monomer G2, an alignment agent with good storage stability can be obtained for different dianhydride monomers G1. Moreover, the liquid crystal alignment film has a higher voltage retention rate, lower image residue, and lower surface roughness, indicating that the present invention has universality for different dianhydride monomers G1.
[0211] As can be seen from the test results of Examples 1, 29-33 and Comparative Examples 6-7, if the dianhydride monomers are all highly reactive anhydrides, the reaction between the anhydride and the diamine is too rapid, and the rigid structure of the highly reactive anhydride makes the polymer toughness insufficient, which degrades the performance of the orientation film.
[0212] Table 5 shows the test results of Examples 1, 34-38, and Comparative Examples 8-9. The only difference between Examples 34-38, Comparative Examples 8-9 and Example 1 is the relevant parameters in Table 5, mainly the type of dianhydride monomer G2.
[0213] Table 5
[0214]
[0215] As can be seen from the test results in Table 5, when the preparation method of the present invention is used, and the diamine is kept in excess throughout the reaction process, and a low-reactivity dianhydride is used to react with the diamine first, followed by the addition of a high-reactivity dianhydride monomer G2, an alignment agent with good storage stability can be obtained for different dianhydride monomers G2. Moreover, the liquid crystal alignment film has a higher voltage retention rate, lower image residue, and lower surface roughness, indicating that the present invention has universality for different dianhydride monomers G2.
[0216] As can be seen from the test results of Examples 1, 34-38 and Comparative Examples 8-9, if the dianhydride monomers are all low-activity anhydrides, the segment rigidity of the polymer molecular chain is insufficient and the polymer reaction is slow, which affects the performance of the orientation film.
[0217] Table 6 shows the test results of Example 1 and Comparative Examples 10-11. The difference between Comparative Examples 10-11 and Example 1 lies in the order of addition of dianhydride monomers during the preparation process.
[0218] Table 6
[0219]
[0220] As can be seen from the test results in Table 6, when the highly reactive dianhydride monomer is added first, followed by the less reactive dianhydride monomer, or both are added simultaneously, the storage stability of the orientation agent, the voltage retention rate of the orientation film, image residue, and surface roughness are all degraded compared to the technical solution of this invention. This is mainly because the preparation method of this invention adopts a reaction sequence of less reactive to more reactive monomers, which ensures controllable reaction. It first constructs flexible / medium-rigid segments and then precisely embeds the high-rigidity segments into the molecular chain, thereby optimizing the mechanical and interfacial properties of the orientation film.
[0221] The present invention has been further described above with reference to specific embodiments. However, it should be understood that the specific description herein should not be construed as limiting the nature and scope of the present invention. Various modifications made to the above embodiments by those skilled in the art after reading this specification are all within the scope of protection of the present invention.
Claims
1. A method for preparing polyamic acid, characterized in that, Includes the following steps: Under nitrogen protection, diamine monomers A and B are dissolved in an organic solvent, dianhydride monomer G1 is added and stirred continuously. After the dianhydride monomer G1 is completely consumed by the reaction, dianhydride monomer G2 is added and stirred to obtain the product. Wherein, the ratio of the total molar amount of the diamine monomer A and the diamine monomer B to the total molar amount of the dianhydride monomer G1 and the dianhydride monomer G2 is greater than 1; The reactivity of the dianhydride monomer G1 is less than that of the dianhydride monomer G2, and the reactivity is the relative reaction rate of the ring-opening nucleophilic addition reaction between the anhydride group and the amino group. With the relative reaction rate of pyromellitic dianhydride as 1, the relative reaction rate of dianhydride monomer G1 is <0.3, and the relative reaction rate of dianhydride monomer G2 is ≥0.
6. The diamine monomer A is a diamine monomer without functional groups, and the diamine monomer B is a diamine monomer containing functional groups. The diamine monomer A has a rigid backbone structure and contains no or only substituents that do not affect the rigidity of the main chain; the functional groups in the diamine monomer B include any one or more of hydroxyl, carboxyl, amino, C1-C6 alkoxy, cyano, vinyl, epoxy, mercapto, amide, ester, and fluorine-containing groups. The molar ratio α of the diamine monomer A and the diamine monomer B satisfies 0 < α ≤ 1.0; The dianhydride monomer G1 includes any one of the following compounds: The dianhydride monomer G2 includes any one of the following compounds: 。 2. The method for preparing polyamic acid according to claim 1, characterized in that, The ratio R1 of the total molar amount of diamine monomer A and diamine monomer B to the molar amount of dianhydride monomer G1 satisfies 1.1≤R1≤2.
0.
3. The method for preparing polyamic acid according to claim 1, characterized in that, The molar ratio γ of the dianhydride monomer G2 and the dianhydride monomer G1 satisfies 0.2≤γ≤2.
0.
4. The method for preparing polyamic acid according to claim 1, characterized in that, The ratio δ of the total molar amount of the diamine monomer A and the diamine monomer B to the total molar amount of the dianhydride monomer G1 and the dianhydride monomer G2 satisfies 1.00 < δ ≤ 1.
50.
5. A polyamic acid prepared by the preparation method according to any one of claims 1-4, characterized in that, Includes the following structure: Polymer PAA-AA Polymer PAA-AB Polymer PAA-BB Polymer (PAA-AA)-G2-(PAA-AA) Polymer (PAA-AA)-G2-(PAA-AB) Polymer (PAA-AA)-G2-(PAA-BB) Polymer (PAA-BB)-G2-(PAA-BB) Polymer (PAA-BB)-G2-(PAA-AB) Wherein, G1 and G2 are tetravalent organic groups, A and B are divalent organic groups, and n1, n2, and n3 represent the number of polymerization units, ranging from 50 to 1000.
6. A liquid crystal alignment agent comprising polyamic acid and / or a polyimide obtained by imidizing the polyamic acid, wherein the polyamic acid is the polyamic acid according to claim 5 or the polyamic acid prepared by any one of claims 1-4.
7. A liquid crystal alignment film, characterized in that, It is obtained by coating and baking the liquid crystal alignment agent as described in claim 6.
8. A liquid crystal display element, characterized in that, Includes the liquid crystal alignment film as described in claim 7.
Citation Information
Patent Citations
Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element
CN110178076A
Polyimide substance and application thereof
CN115141372A